Learning Experiences in Small Group Discussion in the Third Semester of English Education Students - Syafitri, Widya (JOLLT Journal of Languages and Language Teaching, 2023)
Collaborative learning remains to be a range that is progressively getting consideration in academic fields.Â As it has many advantages to individual student learning. One of collaborative learning methods is small group discussion. Furthermore, this study was aimed at describing the result of studentsâ€™ evaluation of the learning experiences in a small group discussion in the third semester of English education students in UIN Sjech M. Djamil Djambek (SMDD) Bukittinggi based on the Students Experience Questionnaire (SEQ). This study is categorized as a quantitative study. This descriptive quantitative research collected data by distributing a questionnaire to the third-semester students. The issues addressed are studentsâ€™ learning experiences in doing a small group discussion. Based on the data analysis, the result showed that the third-semester students had a good learning experience in all aspects; in the good teaching scale, understanding of learning, assessment, appropriate workload, the skills of affective and psychomotor, motivation, and satisfaction with the module used during the learning process through the small group discussion. However, the teachers still need to improve their ability in managing small group discussions.